2016
DOI: 10.3390/jcm5070060
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Remote Ischemic Preconditioning on Arterial Stiffness and Heart Rate Variability in Patients with Angina Pectoris

Abstract: Remote ischemic preconditioning (RIPC) is the set of ischemia episodes that protects against subsequent periods of prolonged ischemia through the cascade of adaptive responses; however, the mechanisms of RIPC are not entirely clear. Here, we aimed to study the impact of RIPC in patients with stable angina pectoris and compare it with healthy individuals with respect to arterial stiffness and heart rate variability. In the randomized, sham-controlled, crossover blind design study, a group of 30 coronary heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
7
19
0
Order By: Relevance
“…However, a recent study could only detect HRV changes in patients with coronary disease but not in healthy volunteers (Zagidullin et al. ). Moreover, RIPC in healthy volunteers attenuated I/R sympathetic activation following ischemia/reperfusion limb injury (Lambert et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study could only detect HRV changes in patients with coronary disease but not in healthy volunteers (Zagidullin et al. ). Moreover, RIPC in healthy volunteers attenuated I/R sympathetic activation following ischemia/reperfusion limb injury (Lambert et al.…”
Section: Introductionmentioning
confidence: 99%
“…RIPC in conscious volunteers also induces vasodilatation of the contralateral artery (right brachial artery) and improved parasympathetic activity as measured using heart rate variability (HRV) (Enko et al 2011). However, a recent study could only detect HRV changes in patients with coronary disease but not in healthy volunteers (Zagidullin et al 2016). Moreover, RIPC in healthy volunteers attenuated I/R sympathetic activation following ischemia/ reperfusion limb injury (Lambert et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the mechanism of the protective effect of RIPC is still unclear. Some studies have suggested that the mechanism of renal protection by RIPC is that it can play a role in anti-inflammatory, antioxidant, and nerve and humoral pathways by activating a variety of factors [42-44]. Recently studies suggested that RIPC could reduce renal damage in CIN through the activation of the tumor necrosis factor-α/neural factor-κB pathway and then increases the expression of renal enzymes and plays the role of anti-inflammatory, antiapoptosis, and antioxidant protection of the kidney [45].…”
Section: Discussionmentioning
confidence: 99%
“…To the authors' knowledge, only one study has focused on the effects of RIPC on arterial stiffness parameters. Zagidullin et al 6 found that RIPC reduced MAP, AIx, and systolic blood pressure in patients with stable angina pectoris. Multiple factors have been found to contribute to the mechanisms of RIPC, with some being directly connected to endothelial function.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…Moreover, the effect of RIPC on lowering AIx and peripheral and central systolic blood pressures, as well as pulse pressure in patients with angina pectoris, has been described by Zagidullin et al, who also linked the effect to improvement in endothelial function. 6 Taking the above data into account, the chance of seeing the effect of RIPC on arterial stiffness in other populations, such as patients undergoing vascular surgery, is realistic.…”
Section: Subgroup Analysismentioning
confidence: 99%